2006
DOI: 10.1645/ge-574r1.1
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Approach to the Experimental Transmission Success of Echinostoma Friedi (Trematoda: Echinostomatidae) in Rats

Abstract: Using a range of parameters, the ability of rats (Rattus norvegicus) to successfully transmit Echinostoma friedi to the next host was examined under experimental conditions. The concept of Experimental Transmission Success (T M ), defined as the number of hosts that become successfully infected after exposure to a number of infective stages produced by a previous host per unit of inoculation at which this latter host was exposed, was introduced. Using data for the egg output and miracidium hatching and infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Our previous studies (Machado e Silva et al 1991, Maldonado Jr. et al 1994) and others (Ribeiro et al 1998) have demonstrated that available knowledge can be learnt from wild rodents experimentally infected under laboratory conditions. In addition, the success of S. mansoni development in a wild rodent may provides a measure to assay its susceptibility or ability to maintain this parasite (Toledo et al 2006). A. cursor possesses many qualities which would be highly desirable in a laboratory animal: it is capable of breeding successfully under simple conditions of management and displays good adaptation to laboratory facilities (D'Andrea et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies (Machado e Silva et al 1991, Maldonado Jr. et al 1994) and others (Ribeiro et al 1998) have demonstrated that available knowledge can be learnt from wild rodents experimentally infected under laboratory conditions. In addition, the success of S. mansoni development in a wild rodent may provides a measure to assay its susceptibility or ability to maintain this parasite (Toledo et al 2006). A. cursor possesses many qualities which would be highly desirable in a laboratory animal: it is capable of breeding successfully under simple conditions of management and displays good adaptation to laboratory facilities (D'Andrea et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the interest in describing and modeling the population dynamics of helminths has concerned parasite fecundity in the definitive host (Toledo et al 2006). However, morphological characteristics of adult worms demonstrate that phenotypic plasticity is an important means through which helminths respond to changes in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The elimination of E. trivolvis from mice occurs within 2-3 wpi (Weinstein and Fried 1991) , while in hamsters worms survived for up to 123 days postinfection (dpi) (Mabus et al 1988) . Similarly, E. friedi was able to survive for at least 12 wpi in hamsters, whereas the infection was expelled at 3-4 wpi in rats (Toledo et al 2003a(Toledo et al , 2006aMuñoz-Antoli et al 2004) . Differences in the pattern of worm expulsion between strains of mice also have been observed.…”
Section: Manifestations Of Resistance To Infectionmentioning
confidence: 95%
“…There is evidence suggesting a role of the host immune response in the regulation of the fecundity of echinostomes. Differences in egg counts in relation to the host species have been reported for E. caproni (Toledo et al 2004a) , E. trivolvis (Franco et al 1986) , and E. friedi (Muñoz-Antoli et al 2004 ;Toledo et al 2006a) . In some cases, the differences observed in the egg output could be attributed to the different number of worms established in each host species in relation to the host-parasite compatibility.…”
Section: Manifestations Of Resistance To Infectionmentioning
confidence: 97%
See 1 more Smart Citation